PENERAPAN PERSONAL HYGIENE KARYAWAN HOUSEKEEPING DEPARTMENT HOTEL TJOKRO PEKANBARU - Alamsyah "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tjokro Pekanbaru Hotel or also called PT. Sukses Anugerah Selaras is a national private company engaged in hospitality services or lodging. Tjokro Pekanbaru Hotel is one of the Grand Tjokro Hotels Indonesia collections which include Grand Tjokro Klaten hotels, Grand Tjokro Yogyakarta, Tjokro Hotel Pekanbaru, Grand Tjokro Jakarta, Grand Tjokro Bandung, and Tjokro Style Yogyakarta. Before becoming a hotel, this hotel used to be known as PT. SUKSES ANUGERAH SELARAS. And in November 2013 the Tjokro Pekanbaru hotel was established in collaboration with Kagum Hotels Indonesia. Tjokro Pekanbaru Hotel had once been under the auspices of KAGUM Hotels for 1 year, but in July 2015 the Tjokro Pekanbaru hotel broke away from KAGUM Hotels Indonesia. Tjokro Pekanbaru hotel activities are largely determined by the performance of qualified employees. In this discussion this research examines the importance of the role and application of body hygiene of employees or what is commonly called personal hygiene at housekeeping department employees. While data collection techniques in this study use observation, interviews and documentation. Based on the results of the research that has been done, for the whole of the results of the interview answers said that based on the results of the study it can be concluded that the application of Personal Hygiene employees of the Housekeeping Department of Tjokro Pekanbaru hotel is not in accordance with the existing standardsKeywords: Personal Hygiene, Housekeeping, Hotels